Penggunaan model Think Pair Share untuk meningkatkan kemampuan berpikir kritis siswa kelas VI SD Negeri Pecuk - Wakhidah, Wakhidah (Jurnal Kualita Pendidikan, 2024)
Many grade VI students of Pecuk 1 Elementary School whose scores are still below the KKM are the reasons for conducting this research. One effort that can be made to improve learning outcomes is to apply the Think Pair Share (TPS) Cooperative Learning Model. The object of the research is the entire process and results of PKn learning with the application of the Think Pair Share (TPS) Cooperative model. The instruments used are observation sheets. The data analysis technique is descriptive quantitative. The results obtained are that the critical thinking skills of grade VI students of Pecuk 1 Elementary School increased after the use of the Think Pair Share Cooperative model in PKn learning with the material of Practicing Pancasila Values. This increase is evident in the increase in students' critical thinking skills from an average pre-action score of 64.8 to 69.6 in cycle I and increasing to 79.2 in cycle II. Students who achieved the success criteria experienced an increase of 45% in pre-action to 60% in cycle I and increasing to 90% in cycle II. The results of the observation also showed an increase in student activity from cycle I to cycle II, namely 30% of students' activities increased, including: students were active in learning, students were freer to search for and collect the desired information, and students also had more opportunities to learn with friends.